Brown adipose tissue mapping in rats with combined intermolecular double‐quantum coherence and Dixon water–fat MRI. (15th July 2013) - Bao, Jianfeng; Cui, Xiaohong; Cai, Shuhui; Zhong, Jianhui; Cai, Congbo; Chen, Zhong
<x xml:space="preserve">Abstract</x> Brown adipose tissue (BAT) is a promising therapeutic target in obesity studies. Recently, MRI has been proposed for the mapping of BAT. However, because of the limitation of spatial resolution, similar to the existing positron emission tomography and computed tomography techniques for BAT detection, it fails to distinguish BAT cells when they are mixed with other cells. In this work, a new MRI method is proposed, combining intermolecular double‐quantum coherence and the chemical shift‐encoded Dixon method. Its contrast depends on the water to fat ratio at the cellular scale, which is smaller than the imaging voxel size. The feasibility of this MRI method was shown with computer simulations and phantoms, and preliminary imaging of BAT of rats at 7 T. Both computer simulations and experimental results are consistent with theoretical predictions. The method provides a novel contrast mechanism and can map BAT distribution exclusively. In particular, a mixture of BAT cells and white adipose tissue cells was detected in an older rat, which was undetectable by other noninvasive methods. This method may be applicable to a wide range of uses in BAT‐related studies, including the formation and variation of BAT. Copyright © 2013 John Wiley & Sons, Ltd.